2000
DOI: 10.4049/jimmunol.164.11.5981
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Reactive Metal Compounds Inhibit NF-κB Activation by Blocking IκB Kinase

Abstract: Gold compounds are used in the treatment of rheumatoid arthritis. NF-κB is a transcription factor implicated in the expression of many inflammatory genes. NF-κB is activated by signal-induced phosphorylation and subsequent degradation of inhibitory IκB (inhibitory protein that dissociates from NF-κB) proteins, and a multisubunit IκB kinase (IKK) has been identified previously. We tested the effect of various gold compounds on the activation of NF-κB and IKK in LPS-stimulated RAW 264.7 mouse macrophages. A lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(187 citation statements)
references
References 64 publications
6
180
0
1
Order By: Relevance
“…Together these data indicated that if zinc inhibits NFB activity, such inhibition occurs via blocking of IB kinase (IK) activity. Indeed, recent studies have demonstrated that thiol-reactive metal compounds inhibit Page 22 of 57 A c c e p t e d M a n u s c r i p t 22 NFB activation by blocking IK [60]. In our study, we also detected that zinc supplementation significantly inhibited phosphorylation of IB while increasing its total level.…”
Section: Discussionsupporting
confidence: 72%
“…Together these data indicated that if zinc inhibits NFB activity, such inhibition occurs via blocking of IB kinase (IK) activity. Indeed, recent studies have demonstrated that thiol-reactive metal compounds inhibit Page 22 of 57 A c c e p t e d M a n u s c r i p t 22 NFB activation by blocking IK [60]. In our study, we also detected that zinc supplementation significantly inhibited phosphorylation of IB while increasing its total level.…”
Section: Discussionsupporting
confidence: 72%
“…AF is an antirheumatic drug with immunosuppressive and anti-inflammatory properties and it is known to inhibit NF-kB activation by blocking IkB-kinase (Jeon et al, 2000). NF-kB is important in cell survival, acting as a transcription factor to induce the expression of antiapoptotic IAP genes (Lee & Collins, 2001).…”
Section: Is Kim Et Almentioning
confidence: 99%
“…Recombinant glutathione S-transferase (GST)-IκBα containing N-terminal 54 residues of IκBα and recombinant human TNF were prepared by expression in Escherichia coli as described previously (Jeon et al, 2000). Expression vectors for FLAG-tagged IKKβ and IKKβ (S177/181E) were kindly provided by Dr. F. Mercurio (Signal Pharmaceuticals, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected with expression vectors for IKKβ and their mutants using Fugene 6 (Roche Molecular Biochemicals, Mannheim, Germany) and incubated for 48 h. Preparation of cytoplasmic extracts and immunoprecipitation were performed as described (Byun et al, 2002). Kinase activity was measured in reaction mixtures containing 10 µM ATP, [γ-32 P]ATP (2-5 µCi) and GST-IκBα (1 µg) (Jeon et al, 2000). Reaction products were analyzed by SDS-PAGE on a 12.5% gel and electrophoretically transferred to nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation